1998
DOI: 10.1038/nbt0598-473
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of a starch-granule–bound protein leads to modified starch and repression of cold sweetening

Abstract: We have cloned a gene involved in starch metabolism that was identified by the ability of its product to bind to potato starch granules. Reduction in the protein level of transgenic potatoes leads to a reduction in the phosphate content of the starch. The complementary result is obtained when the protein is expressed in Escherichia coli, as this leads to an increased phosphate content of the glycogen. It is possible that this protein is responsible for the incorporation of phosphate into starch-like glucans, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
241
1
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 244 publications
(255 citation statements)
references
References 16 publications
12
241
1
1
Order By: Relevance
“…Nielsen et al (1994) have shown that potato tuber starch is phosphorylated during biosynthesis. This result, in combination with the more recent findings (Lorberth et al, 1998;Yu et al, 2001;Ritte et al, 2002), suggests that phosphate incorporation during starch synthesis somehow determines the degradability of the starch particle. However, it is not yet known whether phosphorylation of starch is restricted to the period of biosynthesis.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Nielsen et al (1994) have shown that potato tuber starch is phosphorylated during biosynthesis. This result, in combination with the more recent findings (Lorberth et al, 1998;Yu et al, 2001;Ritte et al, 2002), suggests that phosphate incorporation during starch synthesis somehow determines the degradability of the starch particle. However, it is not yet known whether phosphorylation of starch is restricted to the period of biosynthesis.…”
supporting
confidence: 62%
“…However, the analyses of plants with reduced GWD activity indicate that the phosphorylation of starch affects its in vivo degradability. Starch breakdown is strongly impaired in GWD antisense potato plants and in the GWDdeficient starch-excess 1 (sex1) mutants of Arabidopsis (Lorberth et al, 1998;Yu et al, 2001;Ritte et al, 2003). The link between phosphorylation and degradation of starch is presently poorly understood.…”
mentioning
confidence: 99%
“…One of the important aims of this work was to produce amylopectins with altered branching structures, and then to try and relate this to altered physical properties of the starches. This may be difficult as the physical properties of the starches are also greatly affected by the phosphate content [27] and, therefore, as both the branching of the amylopectin and the phosphate contents are altered it would be difficult to separate out the effect of altered branching from alterations in phosphate contents.…”
Section: Discussionmentioning
confidence: 99%
“…In potato tuber starch Ϸ0.1-0.5% of the glucose moieties are phosphorylated. The amount of phosphate monoesters in starch strongly influences its physicochemical properties (2) and, therefore, affects the ability of different starches to be used by industry.…”
mentioning
confidence: 99%